2017
DOI: 10.3389/fnhum.2017.00044
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial Direct Current Stimulation over the Dorsolateral Prefrontal Cortex in Schizophrenia: A Quantitative Review of Cognitive Outcomes

Abstract: Cognitive deficits are a core and disabling feature of psychotic disorders, specifically schizophrenia. Current treatments for impaired cognition in schizophrenia remain insufficient. Recent research suggests transcranial direct current stimulation (tDCS) targeting the dorsolateral prefrontal cortex can potentiate cognitive improvements in healthy individuals and those with psychiatric conditions, such as schizophrenia. However, this burgeoning literature has not been quantitatively evaluated. Through a litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(15 citation statements)
references
References 46 publications
0
15
0
Order By: Relevance
“…Just as not all antipsychotics produce the same improvement in a specific symptom, the different stimulation paradigms may not affect the same symptom clusters. The large effect of for the BACS in the tDCS group is intriguing given the emerging literature of anodal tDCS applied to left prefrontal cortex for remediating cognitive deficits in patients with schizophrenia (7, 29). We performed an exploratory analysis to understand to what extent this effect on cognition was a result of the significantly different mean ages across the three groups.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Just as not all antipsychotics produce the same improvement in a specific symptom, the different stimulation paradigms may not affect the same symptom clusters. The large effect of for the BACS in the tDCS group is intriguing given the emerging literature of anodal tDCS applied to left prefrontal cortex for remediating cognitive deficits in patients with schizophrenia (7, 29). We performed an exploratory analysis to understand to what extent this effect on cognition was a result of the significantly different mean ages across the three groups.…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for this discrepancy are uncertain but it is notable that the outcomes of these two studies differ primarily in the magnitude of the placebo response. Other studies examining the efficacy of tDCS for the treatment of psychiatric disorders have found mixed results (6, 7). …”
Section: Introductionmentioning
confidence: 99%
“…Even including repetitive TMS trials, with a total of 33 studies, a particular effect of NIBS on cognition could not be driven, in particular for the heterogeneity of the studies protocol and the variability of cognitive measures evaluated ( Hasan et al, 2016 ). A more recent and specific review on effects of tDCS on cognition included six studies and suggested a small to positive effects of this NIBS modality on working memory and attention ( Mervis et al, 2017 ). However, the data for attention was extracted from one study alone ( Smith et al, 2015 ), which may represent a bias to confirm the specificity of tDCS on this cognitive measure.…”
Section: Discussionmentioning
confidence: 99%
“…Since the human DLPFC and the rodent mPFC are involved in executive functions and working memory [43], transcriptional changes in the mPFC of the miR-137 Tg mice would cause deficits of cognitive function. Interestingly, we found that synaptogenesis signaling pathway, inflammatory-related signaling and inter-cellular-related signaling were highly ranked in the commonly changed pathways between the mPFC in the miR-137 Tg mice and those of the postmortem DLPFC in patients with schizophrenia with short DOI (Table 1).…”
Section: Discussionmentioning
confidence: 99%